A case of leukaemia cutis in a dog with T‐cell chronic lymphocytic leukaemia - Hyeona Bae; Ji‐Seon Yoon; Eulsoo Choi; Sang‐Hyun Kim; Dong‐In Jung; Jinho Park; Sang‐Ki Kim; Dae Young Kim; DoHyeon Yu (Veterinary Medicine and Science, 2022)
Abstract Leukaemia cutis (LC) is the infiltration of neoplastic leukocytes into the skin, characterised by haemorrhagic papules, nodules, and plaques. LC has been reported in human leukaemia patients, but it is extremely rare in dogs. A 13‐year‐old spayed female Golden Retriever that was previously diagnosed with chronic lymphocytic leukaemia was managed with chlorambucil (20 mg/m2 orally, every 2 weeks) and prednisolone (2 mg/kg orally, every other day) for 8 months; however, immunosuppression was temporarily discontinued because of a bacterial urinary tract infection. Cutaneous signs, including multifocal ecchymosis and white plaques, appeared 1 month after cessation of chemotherapy. Histopathological examination revealed small‐ to intermediate‐sized lymphocytes with mild atypia in a perivascular to interstitial pattern within the superficial dermis. The bands of atypical cells within the superficial dermis were strongly and extensively positive for CD3 on immunohistochemistry. Polymerase chain reaction analysis of the biopsied skin revealed clonal rearrangement of the T‐cell receptor gamma locus gene. Given the evidence of clinical signs, peripheral immunophenotyping, histopathology, immunohistochemistry, and clonal gene arrangement, LC was diagnosed. The lesions disappeared when chemotherapy was restarted but were occasionally observed when chemotherapy was stopped. To the authors’ best knowledge, this is the first case report of LC in a dog.